The Role of Students in Strengthening Religious Moderation through Islamic Religious Education in Indonesia - Farandika Nanda Pratama; Miftakhul Jannah; Fitra Irpandi (LP2M STIT Palapa Nusantara, 2025)
Religious moderation plays an important role in multicultural societies like Indonesia, especially when faced with challenges of intolerance, radicalism, or extremism. Through Islamic Religious Education, students' moderate attitudes can be formed to strengthen tolerance and harmony in the midst of diversity. This research aims to identify and analyze the role of students in strengthening religious moderation through Islamic religious education in Indonesia and the element of novelty in this research is an in-depth exploration of how students can act as agents of change in strengthening moderation with Islamic Religious Education in the midst of challenging times. This research uses a qualitative method of library research type with data collection techniques through understanding theories from books, journals, or other relevant sources. After the data is obtained, it will be studied in depth with descriptive qualitative data analysis techniques that obtain the results of his research, namely students have a strategic role in strengthening religious moderation through Islamic Religious Education in Indonesia. So, students can respond positively to policies regarding religious moderation and realize a harmonious social life.